DIGITAL CONTROL SIMULATION AID - LEONG, ZHENG YAN (Universiti Teknologi PETRONAS, 2021)
The concept of digital twin has been introduced in 2002. The concept has been widely used in many engineering fields mainly for model based engineering systems. The digital twin is digital representation of a physical system in the form of a virtual prototype. However, the problem with the digital twin is the virtual example of a physical dynamic system. This is because the virtual system is gradiently prossesing the latest version configuration operation , maintenance and reliability during the surface of life cycle. Therefore, this work presents the vision toolbox for incorporating digital twin technology in aspect of modules engineering programme. Furthermore, the developed system provides real-time examples with the use of internet of things and many twin technologies. The results presents shows here that the proposed system performs better compared to the conventional twin system.